An Analysis of Intra-Sentential Code Mixing in the YouTube Podcast Video by Timothy Ronald Featuring Agatha Chelsea - Ni Komang Anik Supadmi; Putu Gede Budiartha (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study investigates the phenomenon of intra-sentential code mixing in the YouTube podcast video by Timothy Ronald featuring Agatha Chelsea, titled "Misi Membangun 1000 Sekolah ft Agatha Chelsea". Code mixing, especially within a single sentence, is a common phenomenon in casual spoken interactions among bilingual speakers. This study focuses on identifying the various forms and communicative purposes of intra-sentential code mixing used by the speakers. A qualitative descriptive method was employed, and the data were obtained through observation and transcription of the YouTube podcast. The analysis is based on Hoffman’s theory (1991), which highlights several reasons for code mixing, including discussing certain themes, repeating for explanatory purposes, articulating personal identity, interjection, and emphasizing particular ideas. The findings show that there are 10 instances of intra-sentential code mixing, where Indonesian and English are frequently combined to enhance clarity, fluency, and emotional emphasis. It can be concluded that intra-sentential code mixing is not only a linguistic habit but also a strategic tool for effective communication in digital media, especially among bilingual young adults. This research contributes to broader discussions in digital communication studies by illustrating how code mixing reflects identity, audience engagement, and linguistic creativity.